ChemInform Abstract: Artificial Metalloenzymes in Asymmetric Catalysis: Key Developments and Future Directions. Issue 30 (July 2015) - Pamies, Oscar; Dieguez, Montserrat; Baeckvall, Jan‐E.
Abstract Review: [79 refs.